2011
DOI: 10.1002/chem.201003559
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photochemical Investigations of Tetrasubstituted Alkenes as Molecular Switches—The Effect of Substituents

Abstract: Molecular switches based on helical tetrasubstituted alkenes, substituted with either electron-withdrawing (CF(3), F, CN; 2a-c, 3a,c) or -donating substituents (Me, OMe; 2d,e), have been synthesized from acyclic precursors 4 and 5 in a domino carbopalladation/Stille reaction. This palladium-catalyzed process allowed the rapid assembly of two C-C bonds, two six-membered rings, and the tetrasubstituted double bond in a completely diastereoselective fashion. The electronic effects of the substituents on the overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…[7,[26][27][28][29][30][31][32] Through desymmetrization of our systems, the unidirectionality of the rotary motion has been extensively demonstrated and various stereoisomers have been identified by spectroscopica nd chromatographict echniques fore ach variation in design. [33][34][35][36][37][38][39][40][41][42][43][44] Ak ey aspect of these systems is that the photochemical generation of metastable speciesi sf ollowed by thermally induced isomerizations, for whicht he lifetimes have been tuned through structural changes to range from nanoseconds to years. [34,38,44,45] Hence, overcrowdeda lkenes can be defined as either motors or switchesd epending on the activatione nergy and therefore speed of the thermal isomerization step (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7,[26][27][28][29][30][31][32] Through desymmetrization of our systems, the unidirectionality of the rotary motion has been extensively demonstrated and various stereoisomers have been identified by spectroscopica nd chromatographict echniques fore ach variation in design. [33][34][35][36][37][38][39][40][41][42][43][44] Ak ey aspect of these systems is that the photochemical generation of metastable speciesi sf ollowed by thermally induced isomerizations, for whicht he lifetimes have been tuned through structural changes to range from nanoseconds to years. [34,38,44,45] Hence, overcrowdeda lkenes can be defined as either motors or switchesd epending on the activatione nergy and therefore speed of the thermal isomerization step (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The large number of structural modifications that has been presented by our group and others has expanded the field of molecular design with three generations of photoswitchable overcrowded alkenes, the majority of which exhibits a strong directional preference and functions as rotary motors . Through desymmetrization of our systems, the unidirectionality of the rotary motion has been extensively demonstrated and various stereoisomers have been identified by spectroscopic and chromatographic techniques for each variation in design . A key aspect of these systems is that the photochemical generation of metastable species is followed by thermally induced isomerizations, for which the life‐times have been tuned through structural changes to range from nanoseconds to years .…”
Section: Introductionmentioning
confidence: 99%
“…The deprotection of 20 with K 2 CO 3 in MeOH/CH 2 Cl 2 14 afforded 13 in essentially quantitative yield. Also in this case, examination of the 1 H NMR spectrum of the product obtained after removal of the volatiles revealed that the crude product was free from major contaminants.…”
Section: Resultsmentioning
confidence: 99%
“…Molecules with all-carbon tetrasubstituted alkene structural motifs, such as the estrogen receptor modulators tamoxifen and idoxifene, [1][2][3][4] amongst others (Figure 1A), have displayed significant biological activity and found widespread applications in the pharmaceutical industry. [5][6][7][8][9] Moreover, their unique photoand electrochemical properties have rendered them particularly useful for molecular switches [10][11] and material science. [12][13][14] Despite this rising demand, the stereoselective synthesis of tetrasubstituted alkenes has been a longstanding challenge and as a result only a few synthetic approaches have been reported in recent years.…”
Section: Introductionmentioning
confidence: 99%